Adhesive composition

By modifying the composition of cellulose fibers and resin, using the cellulose type I crystal structure and anionic group of the modified cellulose fibers, the mechanical strength and shear bonding strength of the metal component adhesive in the prior art are solved. Improve the problem and achieve efficient bonding effect and heat shrinkage suppression.

CN115551966BActive Publication Date: 2024-12-13KAO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180032705.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-03
Filing Date
2021-06-01
Publication Date
2024-12-13
Estimated Expiration
2041-06-01

AI Technical Summary

Technical Problem

In the prior art, it is difficult to achieve simultaneously improving mechanical strength and shear bonding strength of the adhesive agent for structural metal components, and heat shrinkage affects the smoothness and bonding of the bonding surface.

Method used

Using a composition of modified cellulose fibers and resin, the modified cellulose fibers have a cellulose type I crystal structure, the average fiber length is less than 1000 nm, the average fiber diameter is more than 1nm and less than 300 nm, and the anionicity is introduced into the cellulose fibers. Groups and modification groups form excellent adhesive compositions to enhance mechanical strength.

Benefits of technology

It achieves the improvement of mechanical strength and shear bonding strength, suppresses heat shrinkage, improves the smoothness and adhesion of the bonding surface, and is suitable for the bonding of metal components of structural bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003917774580000051
    Figure BDA0003917774580000051
  • Figure BDA0003917774580000081
    Figure BDA0003917774580000081
  • Figure BDA0003917774580000101
    Figure BDA0003917774580000101
Patent Text Reader

Abstract

The present invention relates to an adhesive composition comprising (a) modified cellulose fibers and (b) a resin, wherein the (a) modified cellulose fibers have a cellulose I-type crystal structure, an average fiber length of 1000 nm or less, and an average fiber diameter of 1 nm or more and 300 nm or less. According to the present invention, an adhesive composition having excellent mechanical strength such as shear bonding strength can be provided. Such an adhesive composition of the present invention can be used for structural bonding of vehicle assembly products, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition and a bonding method. Background Art

[0002] In recent years, technologies that reduce the burden on the environment have attracted attention, and in the context of this technology, materials using cellulose fibers, which are biomass that exists naturally in large quantities, have attracted attention.

[0003] For example, Patent Document 1 discloses an adhesive composition containing a water-insoluble resin and fine cellulose fibers containing an ionic group and / or a fine cellulose fiber composite in which a modifying group is bonded to fine cellulose fibers containing an ionic group.

[0004] Patent Document 2 discloses an adhesive composition characterized by containing fine fibrous cellulose and a matrix resin satisfying the following conditions (A) to (E).

[0005] (A) The number average fiber diameter is 2 nm or more and 500 nm or less

[0006] (B) Average aspect ratio is 10 or more and 1000 or less

[0007] (C) has cellulose type I crystal structure

[0008] (D) Has anionic functional groups

[0009] (E) A specific polyether amine is bonded to a part or all of the anionic functional groups described in (D).

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2019-94388

[0013] Patent Document 2: Japanese Patent Application Publication No. 2018-44097 Summary of the invention

[0014] The present invention relates to the following [1] to [3].

[0015] [1] An adhesive composition comprising modified cellulose fiber and a resin,

[0016] The modified cellulose fibers have a cellulose I-type crystal structure, an average fiber length of 1000 nm or less, and an average fiber diameter of 1 nm to 300 nm or less.

[0017] [2] A bonding method comprising bonding a structure with an adhesive composition containing modified cellulose fibers and a resin,

[0018] The modified cellulose fibers have a cellulose I-type crystal structure, an average fiber length of 1000 nm or less, and an average fiber diameter of 1 nm to 300 nm or less.

[0019] [3] A bonding method comprising bonding metal parts using an adhesive composition containing modified cellulose fibers and a resin,

[0020] The modified cellulose fibers have a cellulose I-type crystal structure, an average fiber length of 1000 nm or less, and an average fiber diameter of 1 nm to 300 nm or less. DETAILED DESCRIPTION

[0021] The performance required of an adhesive (or adhesive composition) varies depending on the physical properties of the objects to be bonded.

[0022] The present invention relates to an adhesive composition and a bonding method which are excellent in mechanical strength (for example, shear bond strength) when used for metal members of structures.

[0023] According to the present invention, an adhesive composition and a bonding method having excellent mechanical strength (for example, shear bond strength) can be provided.

[0024] The detailed mechanism by which the adhesive composition of the present invention exerts this effect is not clear, but it is speculated that the modified cellulose fiber is present at the interface between the object to be bonded and the resin, so that even if the smoothness of the bonding surface of the object to be bonded (such as metal and / or plastic) is slightly low, the adhesion of the resin to the bonding surface is improved, and the mechanical strength is improved. It is speculated that this is because the thermal shrinkage of the adhesive composition of the present invention is suppressed during bonding.

[0025] The adhesive composition of the present invention contains modified cellulose fiber and resin.

[0026] The modified cellulose fibers have a cellulose I-type crystal structure, an average fiber length of 1000 nm or less, and an average fiber diameter of 1 nm to 300 nm or less.

[0027] [Modified cellulose fiber]

[0028] The modified cellulose fiber of the present invention refers to a cellulose fiber having a cellulose I type crystal structure, an average fiber length of 1000 nm or less, and an average fiber diameter of 1 nm or more and 300 nm or less, in which a modifying group is bonded to the cellulose fiber. The modifying group is preferably bonded to a part or all of the hydroxyl groups of the cellulose fiber, or to a group (-CH 2 OH) is converted into a carboxyl group.

[0029] As the modifying group, it is preferred to contain at least one selected from (a) a hydrocarbon group, (b) a silicone chain, and (c) an alkylene oxide chain. In addition, as the cellulose fiber to which the modifying group is bonded, an anion-modified cellulose fiber is preferred from the viewpoint of the ease of bonding of the modifying group.

[0030] (Anionic modified cellulose fiber)

[0031] Anionically modified cellulose fibers refer to cellulose fibers having anionic groups in the molecule, for example, one or more groups selected from carboxyl groups, (phosphite) groups, and sulfonic acid groups. The introduction of anionic groups into cellulose fibers can be achieved by the method described below. From the viewpoint of availability and effect, anionically modified cellulose fibers having carboxyl groups as anionic groups are preferred, and more preferably, the group (-CH 2 Anionic modified cellulose fibers (referred to as "oxidized cellulose fibers") are obtained by selectively converting anionic groups (OH) into carboxyl groups. It should be noted that the ion (counter ion) paired with the anionic group is preferably a proton.

[0032] As the anionic group content in the anion modified cellulose fiber, from the viewpoint of stable modification group introduction and improving bonding strength by the introduction of modification groups, it is preferably 0.1mmol / g or more, more preferably 0.4mmol / g or more, more preferably 0.6mmol / g or more, more preferably 0.7mmol / g or more, and more preferably 0.8mmol / g or more. In addition, from the viewpoint of improving operability, it is preferably 3mmol / g or less, more preferably 2.5mmol / g or less, more preferably 2mmol / g or less, more preferably 1.9mmol / g or less, more preferably 1.8mmol / g or less, more preferably 1.7mmol / g or less, and more preferably 1.5mmol / g or less. It should be noted that the so-called "anionic group content" refers to the total amount of anionic groups in the glucose constituting the cellulose fiber, specifically measured by the method described in the embodiments described later.

[0033] The anionic group-bonded modifying group of the anionic modified cellulose fiber refers to the anionic group, preferably the carboxyl group, of the anionic modified cellulose fiber. As the bonding mode of the modifying group and the anionic group, ionic bond and / or covalent bond can be cited. As the covalent bond, for example, amide bond, ester bond, and carbamate bond can be cited, preferably amide bond.

[0034] (Modifying Group)

[0035] Examples of the modifying group include (a) a hydrocarbon group, (b) a silicone chain, and (c) an alkylene oxide chain. These modifying groups can be used alone or in combination of two or more and bonded (introduced) to the cellulose fibers.

[0036] (a) Hydrocarbon

[0037] Examples of the hydrocarbon group include monovalent hydrocarbon groups such as chain saturated hydrocarbon groups, chain unsaturated hydrocarbon groups, cyclic saturated hydrocarbon groups, and (heterocyclic) aromatic hydrocarbon groups.

[0038] From the viewpoint of improving the adhesive strength, the number of carbon atoms in the hydrocarbon group is 1 or more, preferably 3 or more, more preferably 8 or more, and even more preferably 10 or more. From the same viewpoint, the number of carbon atoms in the hydrocarbon group is preferably 30 or less, more preferably 22 or less, and even more preferably 18 or less. The hydrocarbon group may have a substituent described below, and a part of the hydrocarbon group may be substituted with a nitride group.

[0039] As the chain saturated hydrocarbon group, a chain saturated hydrocarbon group having 3 to 30 carbon atoms is preferred, and specific examples thereof include propyl, isopropyl, butyl, sec-butyl, tert-butyl, isobutyl, pentyl, tert-pentyl, isopentyl, hexyl, isohexyl, heptyl, octyl, 2-ethylhexyl, nonyl, decyl, dodecyl, tridecyl, tetradecyl, octadecyl, docosyl, and octacosyl.

[0040] The chain unsaturated hydrocarbon group is preferably a chain unsaturated hydrocarbon group having 3 to 30 carbon atoms, and specific examples thereof include propenyl, butenyl, isobutenyl, isoprene, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, dodecenyl, tridecenyl, tetradecenyl and octadecenyl.

[0041] The cyclic saturated hydrocarbon group is preferably a cyclic saturated hydrocarbon group having 3 to 20 carbon atoms, and specific examples thereof include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, cyclododecyl, cyclotridecyl, cyclotetradecyl, and cyclooctadecyl.

[0042] Examples of the aromatic hydrocarbon group include an aryl group and an aralkyl group. The aryl group and the aralkyl group may be substituted with a substituent described below or may be unsubstituted.

[0043] Examples of the heterocyclic aromatic hydrocarbon group include an imidazolyl group.

[0044] The total carbon number of the aryl group is preferably 6 or more and 24 or less. Specific examples of the aryl group include phenyl, naphthyl, anthracenyl, phenanthryl, biphenylyl, triphenylyl, terphenylyl, and groups in which these groups are substituted with a substituent described below.

[0045] The total carbon number of the aralkyl group is preferably 7 to 24. Specific examples of the aralkyl group include benzyl, phenethyl, phenylpropyl, phenylpentyl, phenylhexyl, phenylheptyl, phenyloctyl, and groups in which these groups are substituted with substituents described below.

[0046] The total number of carbon atoms in the imidazolyl group is preferably 3 or more and 24 or less. Specific examples of the imidazolyl group include imidazolyl, methylimidazolyl, ethylimidazolyl, propylimidazolyl, 2-phenylimidazolyl, benzimidazolyl, and groups in which these groups are substituted with a substituent.

[0047] (b) Silicone chain

[0048] The silicone chain is a monovalent group having a siloxane bond as a main chain, and may be accompanied by an alkylene group. The silicone chain may have a substituent described below.

[0049] (c) Alkylene oxide chain

[0050] The so-called alkylene oxide chain is a structure of a (co)polymer containing ethylene oxide (EO) and propylene oxide (PO), and is preferably one or more structures selected from the group consisting of a structure of a polymer containing EO (EO chain), a structure of a polymer containing PO (PO chain), and a structure of a copolymer containing EO and PO in a random or block state ((EO / PO) chain). A hydrocarbon group may be further bonded to the alkylene oxide chain.

[0051] Examples of the alkylene oxide chain include groups represented by the following formula:

[0052] [Chemical formula 1]

[0053]

[0054] (Where R 1 represents a hydrogen atom, a hydrocarbon group having 1 to 6 carbon atoms, or -CH 2 CH(CH 3 )NH 2 EO and PO exist randomly or in blocks, a is 0 or a positive number representing the average number of added moles of EO, and b is 0 or a positive number representing the average number of added moles of PO. However, the case where both a and b are 0 is not included. ).

[0055] In the above formula, a represents the average added molar number of EO, and is preferably 0 or more, more preferably 1 or more, and further preferably 2 or more from the viewpoint of availability and affinity with the resin. From the same viewpoint, it is preferably 100 or less, and more preferably 70 or less.

[0056] In the above formula, b represents the average number of added moles of PO, and is preferably 0 or more, more preferably 1 or more, and further preferably 3 or more from the viewpoint of affinity with the resin, and is preferably 50 or less, and more preferably 40 or less from the viewpoint of availability.

[0057] As R in the above formula 1 Specific examples of the hydrocarbon group having 1 to 6 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, sec-butyl, tert-butyl, isobutyl, pentyl, tert-pentyl, isopentyl, hexyl and isohexyl.

[0058] The formula weight (molecular weight) of the alkylene oxide chain is preferably 500 or more, more preferably 1000 or more, and is preferably 10000 or less, more preferably 7000 or less. The formula weight of the alkylene oxide chain can be calculated from the average number of added moles when producing an amine compound having an alkylene oxide chain described later.

[0059] From the viewpoint of improving the adhesive strength, the content (mol%) of PO in the (EO / PO) chain is preferably 1 mol% or more, more preferably 5 mol% or more, and from the same viewpoint, it is preferably 100 mol% or less, more preferably 95 mol% or less, and further preferably 90 mol% or less. The content of PO in the (EO / PO) chain can be calculated from the average number of added moles when producing the amine compound having an alkylene oxide chain described later.

[0060] The alkylene oxide chain may have the following substituents.

[0061] (d) Further substituents

[0062] It should be noted that the modifying group may further have a substituent. Examples of the substituent include alkoxy groups having 1 to 6 carbon atoms, such as methoxy, ethoxy, propoxy, isopropoxy, butoxy, isobutoxy, sec-butoxy, tert-butoxy, pentyloxy, isopentyloxy, and hexyloxy; alkoxy-carbonyl groups having 1 to 6 carbon atoms, such as methoxycarbonyl, ethoxycarbonyl, propoxycarbonyl, isopropoxycarbonyl, butoxycarbonyl, isobutoxycarbonyl, sec-butoxycarbonyl, tert-butoxycarbonyl, pentyloxycarbonyl, and isopentyloxycarbonyl; halogen atoms, such as fluorine, chlorine, bromine, and iodine; acyl groups having 1 to 6 carbon atoms, such as acetyl and propionyl; aralkyl; aralkyloxy; alkylamino groups having 1 to 6 carbon atoms; dialkylamino groups having 1 to 6 carbon atoms, and hydroxyl groups.

[0063] [Method for producing modified cellulose fibers]

[0064] Modified cellulose fibers can be produced, for example, by introducing anionic groups into raw material cellulose fibers to produce anionic modified cellulose fibers (step 1), and then bonding modifying groups to the anionic groups of the anionic modified cellulose fibers (step 2).

[0065] (Process 1)

[0066] Raw cellulose fiber

[0067] For the cellulose fiber used as the raw material of the anionic modified cellulose fiber, natural cellulose is preferred from an environmental point of view, and examples thereof include wood pulps such as coniferous tree pulp and broadleaf tree pulp; cotton pulps such as cotton lint and lint; non-wood pulps such as straw pulp and bagasse pulp; bacterial cellulose, etc., and any one of them may be used alone or in combination of two or more.

[0068] The average fiber diameter of the raw material cellulose fiber is not particularly limited, but is preferably 5 μm or more, more preferably 7 μm or more, from the viewpoint of operability and cost, and is preferably 500 μm or less, more preferably 300 μm or less from the same viewpoint. The average fiber diameter of the raw material cellulose fiber is obtained by the method described in the examples described later.

[0069] In addition, the average fiber length of the raw material cellulose fiber is not particularly limited, but is preferably 5 μm or more, more preferably 25 μm or more, from the viewpoint of availability and cost, and is preferably 5000 μm or less, more preferably 3000 μm or less from the same viewpoint. The average fiber length of the raw material cellulose fiber can be measured according to the method described in the examples described below.

[0070] Treatment

[0071] (1) Introducing carboxyl groups as anionic groups into cellulose fibers

[0072] Examples of methods for introducing carboxyl groups into cellulose fibers include: a method of oxidizing hydroxyl groups of cellulose fibers to convert them into carboxyl groups; and a method of reacting hydroxyl groups of cellulose fibers with at least one selected from a compound having a carboxyl group, an acid anhydride of a compound having a carboxyl group, and derivatives thereof.

[0073] As a method for oxidizing the hydroxyl groups of cellulose fibers, for example, there can be mentioned a method described in Japanese Patent Application Publication No. 2015-143336 or Japanese Patent Application Publication No. 2015-143337, in which an oxidizing agent such as sodium hypochlorite and a bromide such as sodium bromide are reacted with the raw material cellulose fibers using 2,2,6,6-tetramethyl-1-piperidine-N-oxide (TEMPO) as a catalyst. By oxidizing the cellulose fibers using TEMPO as a catalyst, the group at the C6 position of the glucose in the structural unit of the cellulose fibers can be selectively converted into a carboxyl group, thereby obtaining the aforementioned oxidized cellulose fibers.

[0074] The compound having a carboxyl group for introducing a carboxyl group into the cellulose fiber is not particularly limited, and specific examples thereof include halogenated acetic acid, and examples of the halogenated acetic acid include chloroacetic acid and the like.

[0075] The anhydrides of compounds having carboxyl groups and their derivatives used for introducing carboxyl groups into cellulose fibers are not particularly limited, and examples thereof include anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride and adipic anhydride, imides of anhydrides of compounds having carboxyl groups, and derivatives of anhydrides of compounds having carboxyl groups. These compounds may be substituted with a hydrophobic group.

[0076] (2) Introducing sulfonic acid groups or (phosphite) groups as anionic groups into cellulose fibers

[0077] Examples of a method for introducing sulfonic acid groups into cellulose fibers include a method of adding sulfuric acid to cellulose fibers and heating the fibers.

[0078] Examples of methods for introducing (phosphite) groups into cellulose fibers include: a method of mixing a powder or aqueous solution of (phosphite) or a (phosphite) derivative with dry or wet cellulose fibers; a method of adding an aqueous solution of (phosphite) or a (phosphite) derivative to a dispersion of cellulose fibers; etc. In the case of adopting these methods, generally, after mixing or adding a powder or aqueous solution of (phosphite) or a (phosphite) derivative, a dehydration treatment or a heating treatment is performed.

[0079] (Process 2)

[0080] The introduction of a modifying group into the anionic group of the anionic modified cellulose fiber can be achieved by reacting the anionic modified cellulose fiber with a compound for introducing a modifying group into the anionic group (referred to as a "modifying compound"). As a method for introducing a modifying group, in the case of (1) introduction via an ionic bond, Japanese Patent Publication No. 2015-143336 can be used as a reference, and in the case of (2) introduction via an amide bond, Japanese Patent Publication No. 2015-143337 can be used as a reference.

[0081] After step 2 is completed, post-treatment may be appropriately performed to remove unreacted compounds, etc. As a method for post-treatment, for example, filtration, centrifugation, dialysis, etc. can be used.

[0082] (1) Introduction via ionic bonds

[0083] When the modifying group is introduced via an ionic bond, the anionic modified cellulose fibers and the modifying compound may be mixed, thereby forming an ionic bond between the anionic group contained in the anionic modified cellulose fibers and the amino group of the modifying compound.

[0084] Specifically, when oxidized cellulose fibers are used as anion-modified cellulose fibers and a primary amine having the aforementioned modifying group is used as a modifying compound, the aforementioned modifying group can be introduced into the C6-position carboxyl group of glucose constituting the cellulose fibers via an ionic bond as shown in the following formula (wherein, C 6 R is the carbon atom at position 6 of the glucose constituting the cellulose fiber, and R is a modifying group.

[0085] [Chemical formula 2]

[0086]

[0087] Modification compounds

[0088] The modifying compound used in the present embodiment may be any compound capable of introducing a desired modifying group, and preferred examples include amine compounds, phosphonium compounds, and guanidine group-containing compounds having the above-mentioned hydrocarbon group, alkylene oxide chain, or silicone chain.

[0089] Amine compounds

[0090] The amine compound is, for example, an amine compound having the aforementioned hydrocarbon group, the aforementioned alkylene oxide chain or the aforementioned silicone chain as a modifying group. The hydrocarbon group or the like is introduced into the anionically modified cellulose fiber via an ionic bond to become a modifying group of the modified cellulose fiber.

[0091] As the amine compound, any one of primary amine, secondary amine, tertiary amine and quaternary ammonium salt compound is all right. As the anion component of the quaternary ammonium salt compound, from the viewpoint of reactivity, preferably halogen ions such as chloride ion and bromide ion, hydrogen sulfate ion, perchlorate ion, tetrafluoroborate ion, hexafluorophosphate ion, trifluoromethanesulfonate ion, hydroxyl ion can be enumerated.

[0092] Amine compounds having a hydrocarbon group

[0093] Specific examples of the amine compound having a hydrocarbon group include primary to tertiary amines such as ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, butylamine, dibutylamine, hexylamine, 2-ethylhexylamine, dihexylamine, trihexylamine, octylamine, dioctylamine, trioctylamine, dodecylamine, didodecylamine, stearylamine, distearylamine, monoethanolamine, diethanolamine, triethanolamine, oleylamine, aniline, octadecylamine, dimethylbehenylamine, benzylamine, naphthylamine, imidazole, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, and 1-(3-aminopropyl)imidazole.

[0094] Examples of the quaternary ammonium salt compound include tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetraethylammonium chloride, tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), tetrabutylammonium chloride, lauryltrimethylammonium chloride, dilauryldimethyl chloride, stearyltrimethylammonium chloride, distearyldimethylammonium chloride, cetyltrimethylammonium chloride, and alkylbenzyldimethylammonium chloride.

[0095] The amine compound having a hydrocarbon group can be prepared by using a commercially available product or by a known method.

[0096] Amine compounds having alkylene oxide chains

[0097] The alkylene oxide chain in the amine compound is preferably bonded to the nitrogen atom of the amine compound directly or via a linking group. As the linking group, a hydrocarbon group is preferred, and an alkylene group having a carbon number of preferably 1 to 6, more preferably 1 to 3 can be cited. As the alkylene group, for example, an ethylene group and a propylene group are preferred.

[0098] Examples of the amine having an alkylene oxide chain include compounds represented by the following formula (i):

[0099] [Chemical formula 3]

[0100]

[0101] R in formula (i) 1 , a and b and R in the above formula representing an example of an alkylene oxide chain 1 , a and b are the same.

[0102] The amine compound having an alkylene oxide chain can be prepared according to a known method. For example, after adding a desired amount of ethylene oxide or propylene oxide to a propylene glycol alkyl ether, the hydroxyl terminal is aminated. If necessary, the terminal can be converted into a hydrogen atom by cleaving the alkyl ether with an acid. The preparation methods of these can refer to Japanese Patent Laid-Open No. 3-181448, and the details of the amine compound are recorded in Japanese Patent No. 6105139.

[0103] As the amine compound having an alkylene oxide chain, for example, a commercially available product can be suitably used. Specific examples thereof include Jeffamine M-2070, Jeffamine M-2005, Jeffamine M-2095, Jeffamine M-1000, Jeffamine M-600, Surfoamine B200, Surfoamine L100, Surfoamine L200, Surfoamine L207, Surfoamine L300, Surfoamine B-100, XTJ-501, XTJ-506, XTJ-507, XTJ-508, M3000, Jeffamine ED-900, Jeffamine ED-2003, Jeffamine D-2000, Jeffamine D-4000, XTJ-510, Jeffamine T-3000, Jeffamine T-5000, XTJ-502, XTJ-509, XTJ-510, etc., and SUNBRIGHT MEPA-10H, SUNBRIGHT MEPA-20H, SUNBRIGHT MEPA-50H, SUNBRIGHT MEPA-10T, SUNBRIGHT MEPA-12T, SUNBRIGHT MEPA-20T, SUNBRIGHT MEPA-30T, SUNBRIGHT MEPA-40T, etc. manufactured by NOF Corporation. These may be used alone or in combination of two or more.

[0104] Amine compounds with silicone chains

[0105] For example, the amine compound includes a compound having a structure in which an amino group is bonded to the skeleton of a silicone chain via an alkylene group or the like. In this specification, the amine compound is sometimes referred to as "amino-modified silicone". Amino-modified silicone can be prepared using a commercial product or a known method. Only one amino-modified silicone may be used, or two or more amino-modified silicones may be used.

[0106] As the amino-modified silicone, TSF4703 (dynamic viscosity: 1000, amino equivalent: 1600), TSF4708 (dynamic viscosity: 1000, amino equivalent: 2800) manufactured by Momentive Performance Materials, SS-3551 (dynamic viscosity: 1000, amino equivalent: 1600), SF8457C (dynamic viscosity: 1200, amino equivalent: 1800), SF8417 (dynamic viscosity: 1200, amino equivalent: 1700), BY16-209 (dynamic viscosity: 500, amino equivalent: 1800), BY16-892 (dynamic viscosity: 1500, amino equivalent: 2000), BY16-898 (dynamic viscosity: 2000, amino equivalent: 2900) manufactured by Dow Corning-Toray Silicone Co., Ltd. 00), FZ-3760 (dynamic viscosity: 220, amino equivalent: 1600), KF8002 (dynamic viscosity: 1100, amino equivalent: 1700), KF867 (dynamic viscosity: 1300, amino equivalent: 1700), KF-864 (dynamic viscosity: 1700, amino equivalent: 3800), BY16-213 (dynamic viscosity: 55, amino equivalent: 2700), BY16-853U (dynamic viscosity: 14, amino equivalent: 450). In parentheses, the dynamic viscosity is the measured value at 25°C (unit: mm 2 / s), and the unit of amino equivalent is g / mol.

[0107] Compounds containing guanidine

[0108] The compound containing a guanidine group is, for example, a guanidine compound having the aforementioned hydrocarbon group, the aforementioned silicone chain, or the aforementioned alkylene oxide chain as a modifying group, and the hydrocarbon group or the like is introduced into the anionic modified cellulose fiber via an ionic bond to become a modifying group of the modified cellulose fiber. Examples of the compound containing a guanidine group include diphenylguanidine, xylylguanidine, 1,2,3-triphenylguanidine, aminoguanidine, and arginine.

[0109] Reaction conditions, etc.

[0110] Regarding the amount of the modifying compound used, from the viewpoint of reactivity, the amount of the amino groups in the modifying compound is preferably 0.01 mol or more, more preferably 0.1 mol or more, further preferably 0.5 mol or more, further preferably 0.7 mol or more, further preferably 1 mol or more, relative to 1 mol of the carboxyl groups possessed by the oxidized cellulose fibers, and from the viewpoint of product purity, it is preferably 50 mol or less, more preferably 20 mol or less, further preferably 10 mol or less. When the modifying compound has a plurality of amino groups, it is used so that the total number of moles of the amino groups is the above number of moles.

[0111] When mixing, a solvent is preferably used. As a solvent, a solvent in which the compound used is dissolved is preferably selected, for example, methanol, ethanol, isopropyl alcohol (IPA), N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N,N-dimethylacetamide, tetrahydrofuran (THF), acetone, methyl ethyl ketone (MEK), cyclohexanone, ethyl acetate, acetonitrile, dichloromethane, chloroform, toluene, acetic acid, 1-methoxy-2-propanol (PGME), water, etc., and one of them can be used alone or in combination of two or more.

[0112] From the viewpoint of the reactivity of the compound, the temperature during mixing is preferably 0° C. or higher, more preferably 5° C. or higher, and further preferably 10° C. or higher. From the viewpoint of suppressing the coloration of the modified cellulose fiber, it is preferably 50° C. or lower, more preferably 40° C. or lower, and further preferably 30° C. or lower. The mixing time can be appropriately set depending on the types of the compound and the solvent used, but from the viewpoint of the reactivity of the compound, it is preferably 0.01 hours or higher, more preferably 0.1 hours or higher, and from the viewpoint of productivity, it is preferably 48 hours or lower, and more preferably 24 hours or lower.

[0113] (2) Introduction via amide bond

[0114] When the modifying group is introduced via an amide bond, the anionic modified cellulose fibers and the modifying compound may be mixed in the presence of a known condensing agent, thereby forming an amide bond between the anionic group contained in the anionic modified cellulose fibers and the amino group of the modifying compound.

[0115] Specifically, when oxidized cellulose fibers are used as anion-modified cellulose fibers and a primary amine having the aforementioned modifying group is used as a modifying compound, the aforementioned modifying group can be introduced into the C6 carboxyl group of glucose constituting the cellulose fibers via an amide bond as shown in the following formula (wherein, C 6R is the carbon atom at position 6 of the glucose constituting the cellulose fiber, and R is a modifying group.

[0116] [Chemical formula 4]

[0117]

[0118] Modification compounds

[0119] The modifying compound used in the present embodiment may be any compound capable of introducing a desired modifying group, and preferably, an amine compound having the above-mentioned hydrocarbon group, alkylene oxide chain, or silicone chain is used.

[0120] Amine compounds

[0121] The amine compound is, for example, an amine compound having the aforementioned hydrocarbon group, the aforementioned alkylene oxide chain, or the aforementioned silicone chain as a modifying group. The hydrocarbon group or the like is introduced into the anionically modified cellulose fiber via an amide bond to become a modifying group of the modified cellulose fiber.

[0122] Examples of the amine compound include primary amines and secondary amines. Specific examples of the amine compound include primary amines and secondary amines among the amine compounds having a hydrocarbon group, amine compounds having an alkylene oxide chain, and amine compounds having a silicone chain exemplified in the aforementioned "(1) Method of introduction via ionic bond".

[0123] Reaction conditions

[0124] Regarding the amount of the modifying compound used, from the viewpoint of improving reactivity and bonding strength, the amount of the amino group in the modifying compound is preferably 0.05 mol or more, more preferably 0.1 mol or more, further preferably 0.2 mol or more, further preferably 0.3 mol or more, further preferably 0.5 mol or more, relative to 1 mol of the carboxyl group possessed by the oxidized cellulose fiber, and from the viewpoint of product purity and expellability, the amount is preferably 50 mol or less, more preferably 20 mol or less, further preferably 10 mol or less. When the modifying compound has a plurality of amino groups, it is used so that the total number of moles of the amino groups is the above number of moles.

[0125] As condensing agent, there is no particular limitation, and examples thereof include those described in Synthetic Chemistry Series Peptide Synthesis (Maruzen Publishing) P116 or Tetrahedron, 57, 1551 (2001), for example, chlorinated 4-(4,6-dimethoxy-1,3,5-triazine-2-yl)-4-methylmorpholine (hereinafter sometimes referred to as "DMT-MM"). In addition, the reaction can be carried out by heat treatment without using a condensing agent.

[0126] A solvent may or may not be used in the amidation reaction. When a solvent is used, it is preferred to select a solvent in which the compound to be used dissolves. Specific examples of the solvent include the solvents exemplified in the above-mentioned "(1) Introduction via ionic bonding".

[0127] The reaction time and reaction temperature in the amidation reaction can be appropriately selected according to the types of compounds and solvents used, and are preferably 1 to 24 hours, more preferably 10 to 20 hours, from the viewpoint of reaction rate. In addition, the reaction temperature is preferably 0° C. or higher, more preferably 5° C. or higher, and further preferably 10° C. or higher, from the viewpoint of reactivity. In addition, from the viewpoint of product quality such as coloring, it is preferably 200° C. or lower, more preferably 80° C. or lower, and further preferably 30° C. or lower.

[0128] (Micro-refining process)

[0129] By refining the cellulose fibers at any stage of the method for producing modified cellulose fibers (e.g., before step 1, before step 2, and after step 2), the micron-level cellulose fibers can be refined to the nanometer level. Reducing the average fiber diameter to the nanometer size improves dispersibility in the resin, which is preferred.

[0130] The micronization treatment may be carried out by a known micronization treatment method. For example, in order to obtain modified cellulose fibers having an average fiber diameter of nanometer size, a treatment method using a mill such as a Masscolloider or a treatment method using a high-pressure homogenizer in a medium may be used.

[0131] As the medium, for example, water, methanol, ethanol, propanol, 1-methoxy-2-propanol (PGME) and other alcohols with 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms; acetone, methyl ethyl ketone, methyl isobutyl ketone and other ketones with 3 to 6 carbon atoms; ethyl acetate, butyl acetate and other ketones with 2 to 4 carbon atoms; saturated hydrocarbons or unsaturated hydrocarbons with 1 to 6 carbon atoms; aromatic hydrocarbons such as benzene and toluene; halogenated hydrocarbons such as dichloromethane and chloroform; lower alkyl ethers with 2 to 5 carbon atoms; polar solvents such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide, dimethyl sulfoxide, etc. can be exemplified. They can be used alone or in combination of two or more. The amount of the medium used is sufficient to disperse the modified cellulose fibers. It is preferably used 1 times by mass or more, more preferably 2 times by mass or more, preferably 500 times by mass or less, and more preferably 200 times by mass or less relative to the modified cellulose fibers.

[0132] As the device used in the micronization process, in addition to the high-pressure homogenizer, a known disperser can also be used appropriately. For example, a dissociator, a beater, a low-pressure homogenizer, a grinder, a Masscolloider, a chopper, a ball mill, a jet mill, a short-shaft extruder, a double-shaft extruder, an ultrasonic mixer, a household juicer, etc. can be used. In addition, the solid content of the modified cellulose fiber in the micronization process is preferably below 50% by mass.

[0133] [Properties of modified cellulose fibers]

[0134] The main properties of the modified cellulose fiber of the present invention are as follows.

[0135] (Crystal Structure)

[0136] From the viewpoint of improving the bonding strength, the modified cellulose fiber has a cellulose I type crystal structure. From the viewpoint of improving the bonding strength, the crystallinity of the modified cellulose fiber is preferably 10% or more, more preferably 15% or more, and further preferably 20% or more. In addition, from the viewpoint of raw material availability, it is preferably 90% or less, more preferably 85% or less, further preferably 80% or less, and further preferably 75% or less. It should be noted that in this specification, the crystallinity of the cellulose fiber is the cellulose I type crystallinity calculated based on the diffraction intensity value based on the X-ray diffraction method, and can be measured according to the method described in the embodiments described later. It should be noted that cellulose I type refers to the crystal form of natural cellulose, and the cellulose I type crystallinity refers to the proportion of the amount of crystalline region in the entire cellulose fiber. The presence or absence of a cellulose I type crystal structure can be determined by the presence of a peak at 2θ=22.6° in the X-ray diffraction measurement.

[0137] (Average fiber diameter)

[0138] The modified cellulose fibers are preferably subjected to a micronization treatment to be nano-sized. Therefore, the average fiber diameter of the modified cellulose fibers is preferably 1 nm or more, more preferably 2 nm or more, from the viewpoints of operability, availability and cost, and is preferably 300 nm or less, more preferably 200 nm or less, further preferably 150 nm or less, further preferably 120 nm or less, and further preferably 20 nm or less, from the viewpoints of improving operability, dispersibility and bonding strength.

[0139] (Average fiber length)

[0140] From the viewpoint of improving the bonding strength, the average fiber length of the modified cellulose fibers is preferably 10 nm or more, more preferably 30 nm or more, and further preferably 50 nm or more. On the other hand, from the viewpoint of improving the ejectability and bonding strength, the average fiber length is 1000 nm or less, preferably 500 nm or less, more preferably 300 nm or less, and further preferably less than 150 nm.

[0141] (Average aspect ratio)

[0142] The average aspect ratio of the modified cellulose fibers is preferably 5 or more, more preferably 10 or more, and further preferably 20 or more from the viewpoint of improving the bonding strength. On the other hand, from the viewpoint of improving the ejectability and bonding strength, it is preferably 300 or less, more preferably 200 or less, further preferably 150 or less, further preferably 100 or less, and further preferably 70 or less.

[0143] By setting the average fiber length and the average aspect ratio within the above-mentioned ranges, excellent adhesion between materials having different physical properties (for example, materials having different linear expansion coefficients) can be achieved.

[0144] The average fiber diameter, average fiber length, and average aspect ratio of the modified cellulose fibers were determined by the methods described in Examples below.

[0145] (Bonding amount and introduction rate of modifying groups)

[0146] The bonding amount of the modifying group in the modified cellulose fiber is preferably 0.01 mmol / g or more from the viewpoint of improving the bonding strength, and is preferably 3.0 mmol / g or less from the same viewpoint. When two or more modifying groups are introduced into the modified cellulose fiber as modifying groups at the same time, the bonding amount of the modifying group is preferably within the above range.

[0147] The introduction rate of the modifying group in the modified cellulose fiber is preferably 10 mol% or more from the viewpoint of dispersibility, and the higher the better, preferably 100 mol%. When two or more modifying groups are introduced simultaneously as modifying groups, the total introduction rate is within the range not exceeding 100 mol% as the upper limit, and is preferably within the above range.

[0148] The bonding amount and introduction rate of the modifying group can be adjusted by the type of the modifying compound, the amount added, the reaction temperature, the reaction time, the type of the solvent, etc. The bonding amount (mmol / g) and introduction rate (mol%) of the modifying group refer to the amount and ratio of the modifying group introduced (bonded) to the anionic group in the modified cellulose fiber. For example, when the anionic group is a carboxyl group, the bonding amount and introduction rate of the modifying group in the modified cellulose fiber are calculated by the method described in the examples described later.

[0149] The amount of the modified cellulose fiber in the composition of the present invention is converted by the compounding amount, and is calculated as cellulose (excluding the modifying group, etc.). From the viewpoint of improving the bonding strength, it is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, more preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more. On the other hand, from the viewpoint of the ejectability, it is preferably 30% by mass or less, more preferably 20% by mass or less, more preferably 15% by mass or less, more preferably 10% by mass or less, more preferably 7% by mass or less, even more preferably 5% by mass or less, and even more preferably 3% by mass or less.

[0150] 〔Resin〕

[0151] The resin of the present invention is preferably a water-insoluble resin that is insoluble in water or has very low solubility in water from the viewpoint of use in various structures. Specifically, a resin having a solubility in water at 25° C. of 1 mg or less per 100 g of water is called a water-insoluble resin.

[0152] The above solubility was measured as shown below.

[0153] 100 mg of resin was added to 1 L (25°C) of water, and stirred for 24 hours using a stirring device such as a stirrer. The solution (or suspension) was centrifuged at 25°C and 3000×g for 30 minutes to collect the insoluble residue. The residue was dried at 105°C for 3 days, and the mass after drying (dry mass) was measured. Thereafter, a resin with a dry mass of less than 99 mg was judged to be water-soluble, and a resin with a dry mass of more than 99 mg was judged to be water-insoluble.

[0154] Preferred examples of the resin used in the present invention include resins that have adhesive properties alone and resins that exhibit adhesive properties in combination with a curing agent. The resin may be used alone or in the form of a mixture of two or more resins.

[0155] Specific examples of the resin include epoxy resins, urethane resins, acrylic resins, vinyl chloride resins, phenoxy resins, phenolic resins, urea resins, melamine resins, polyimide resins, unsaturated polyester resins, diallyl phthalate resins, and rubber-based resins.

[0156] Among the resins, curable resins (e.g., epoxy resins, urethane resins, acrylic resins, phenoxy resins, phenolic resins, urea-formaldehyde resins, melamine resins) are preferred from the viewpoint of improving the bonding strength. Depending on the type of the resin, light curing and / or heat curing treatment may be performed. As the resin used in the present invention, a thermosetting resin is preferred.

[0157] The mass ratio of the modified cellulose fiber / resin in the composition of the present invention, calculated by the blending amount and converted to cellulose (excluding modifying groups etc.) (wherein, when the cellulose has anionic groups, converted to anionic modified cellulose), is preferably 0.01 / 100 or more, more preferably 0.05 / 100 or more, more preferably 0.1 / 100 or more, more preferably 0.3 / 100 or more, and even more preferably 0.5 / 100 or more from the viewpoint of improving the adhesive strength, and on the other hand, is preferably 30 / 100 or less, more preferably 20 / 100 or less, more preferably 15 / 100 or less, more preferably 10 / 100 or less, more preferably 7 / 100 or less, even more preferably 5 / 100 or less, and even more preferably 3 / 100 or less from the viewpoint of the ejectability.

[0158] [Other ingredients]

[0159] The adhesive composition of the present invention may contain, as necessary, components known in the adhesive field such as a polymerization initiator, a plasticizer, a stabilizer, a lubricant, and a surfactant. The amount of the components is not particularly limited, and any appropriate amount may be used.

[0160] [Method for producing adhesive composition]

[0161] The adhesive composition of the present invention can be produced, for example, by mixing the modified cellulose fiber described above with the resin described above, etc. Furthermore, a solvent, a curing agent, and the other components described above may be mixed as necessary.

[0162] The method for mixing the components to form the adhesive composition is not particularly limited, and a general method such as a method using a stirrer, an ultrasonic homogenizer, a high-pressure homogenizer, etc. can be mentioned.

[0163] As the solvent that can be used in the production, for example, dimethylformamide, ethyl acetate, methyl methacrylate, ethanol, isopropanol, N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N,N-dimethylacetamide, tetrahydrofuran (THF), a diester of succinic acid and triethylene glycol monomethyl ether, acetone, methyl ethyl ketone (MEK), acetonitrile, dichloromethane, chloroform, toluene, 1-methoxy-2-propanol (PGME), acetic acid, etc. can be mentioned, and one of them can be used alone or two or more of them can be used in combination.

[0164] When a solvent is used, the amount thereof is, for example, preferably 50 parts by mass or more, more preferably 100 parts by mass or more, and preferably 5000 parts by mass or less, more preferably 2000 parts by mass or less, based on 100 parts by mass of the resin.

[0165] The adhesive composition of the present invention and the adhesive using the same are in liquid or solid form (e.g., granular or powdery) at room temperature (25°C). In the case of a solid form, a suitable medium may be added to form a paste, solution, or dispersion. In addition, the adhesive composition may be heated to form a fluid form as required when used.

[0166] <Adhesive composition and bonding method>

[0167] The bonding method of the present invention is a bonding method for bonding a structure (preferably a metal member) using an adhesive composition containing modified cellulose fibers and a resin (i.e., the adhesive composition of the present invention).

[0168] The modified cellulose fibers have a cellulose I-type crystal structure, an average fiber length of 1000 nm or less, and an average fiber diameter of 1 nm to 300 nm or less.

[0169] The bonding method of the present invention includes, for example, applying the adhesive composition of the present invention on a structure (or its component) and bonding it to the other structure (or its component). Such an adhesive composition includes a structural adhesive composition.

[0170] The structural adhesive composition refers to an adhesive composition used in structures such as vehicles and buildings that require mechanical strength, and is preferably used when bonding vehicle assemblies to replace or enhance conventional joining techniques such as welding, nuts and bolts, and rivets. The adhesive composition of the present invention can be used as a structural adhesive by itself, or can be used as a material for an adhesive to be further compounded with other components to obtain an adhesive.

[0171] Examples of vehicles include rockets, airplanes, drones, cars, ships, etc. Specifically, the adhesive bonding method can be used when manufacturing an automobile structure by structurally bonding parts such as a car body and automobile parts, and is particularly suitable for bonding using a process (spot welding bonding process) that uses spot welding and an adhesive.

[0172] There is no particular limitation on the method for applying the adhesive composition to the structure, and examples thereof include methods using a sprayer, a glue gun, a dispenser, a nozzle, a brush, a scraper, etc. Among them, a dispenser is preferably used from the aspect of excellent dischargeability of the adhesive composition of the present invention. When a dispenser is used, a method of discharging the adhesive composition from the dispenser and applying the adhesive composition to the structure can be mentioned.

[0173] After the structure is bonded to the other structure, the bonding can be completed by maintaining the structure at -30 to 200° C. for 1 minute to 3 days, for example.

[0174] The adhesive composition of the present invention has excellent bonding properties with various materials, such as metals such as iron, aluminum, and copper, alloys such as steel and aluminum alloys, plastics such as polypropylene, polyamide, and polyacetal, and fiber-reinforced plastics such as carbon fiber-reinforced plastics and glass fiber-reinforced plastics, rubber, carbon fiber, glass, and ceramics, and has high strength, and can contribute to the lightweighting of structures such as vehicles and the reduction of welding costs. The adhesive composition of the present invention can be suitably used to bond metal components, and can be more suitably used when the bonding surface of the metal component contains aluminum.

[0175] In the bonding method of the present invention, the surface of the structure or its component to which the adhesive composition is applied, i.e., the bonding surface, is preferably a material comprising one or more selected from such metals, plastics, ceramics and glasses, more preferably a material comprising metal and / or plastic, and even more preferably a material comprising metal.

[0176] That is, the bonding method of the present invention is preferably a method of applying the adhesive composition of the present invention on a metal member and bonding the metal member to the other side.

[0177] It should be noted that the metal member refers to a material formed into a shape by metal, and is different from powder or the like.

[0178] The material of the bonding surface used in the bonding method of the present invention preferably includes a material having a linear expansion coefficient of 20×10 -6 / °C or more. Examples of such metals include aluminum and zinc. It is presumed that even if the linear expansion coefficient is high, the adhesive of the present invention suppresses thermal shrinkage, so that the bonding strength is improved.

[0179] More specifically, as the bonding surface of the metal component, for example, steel plate, SPC steel plate, plated steel plate (for example, electrogalvanized steel plate, hot-dip galvanized steel plate, organic surface treated steel plate, alloyed galvanized steel plate, zinc-nickel alloy steel plate, tin-lead steel plate, cationic electroplated steel plate), aluminum plate, aluminum alloy plate (for example, aluminum-manganese alloy plate, aluminum-magnesium alloy plate), magnesium plate. As the bonding surface of plastic, for example, fiber reinforced plastic fiberboard such as carbon fiber reinforced plastic and glass fiber reinforced plastic can be mentioned. As the bonding surface of ceramic, for example, barium titanate, boron nitride, silicon nitride, lead zirconate titanate, aluminum oxide, aluminum nitride, silicon carbide, zinc oxide, zirconium dioxide, ferrite, indium oxide, silicon, etc. can be mentioned. As the bonding surface of glass, for example, soda-lime glass, lead glass, borosilicate glass, quartz glass, etc. can be mentioned. In particular, when the bonding surface of the metal component contains aluminum, the bonding composition of the present invention and the bonding method of the present invention can be suitably used.

[0180] The adhesive composition of the present invention is particularly excellent in adhesion between materials with different physical properties (for example, metal materials with different linear expansion coefficients). -6 / ℃ and the linear expansion coefficient is less than 20×10 -6 / ℃ bonding of metals, etc. Specifically, the bonding strength of the combination of dissimilar metals (such as steel and aluminum alloy, that is, a metal containing iron and a metal containing aluminum, etc.) is also excellent. The metal containing iron can be used as a steel plate, and the metal containing aluminum can be used as an alloy plate. Therefore, the bonding method of this specification can also be suitably applied to a method for bonding dissimilar metals.

[0181] Regarding the above-mentioned embodiment, the present invention further discloses the following adhesive composition and bonding method.

[0182] <1> An adhesive composition contains modified cellulose fibers and a resin, wherein the modified cellulose fibers have a cellulose I-type crystal structure, an average fiber length of 1000 nm or less, and an average fiber diameter of 1 nm or more and 300 nm or less.

[0183] <2> According to the above <1> The composition described in , wherein the average fiber length of the modified cellulose fiber is from 10 nm to 500 nm.

[0184] <3> According to the above <1> or <2> The composition described in , wherein the average fiber length of the modified cellulose fiber is from 10 nm to 300 nm.

[0185] <4> According to the above <1> ~ <3> The composition according to any one of claims , wherein the average fiber length of the modified cellulose fibers is 10 nm or more and less than 150 nm.

[0186] <5> According to the above <1> ~ <4> The composition according to any one of the above, wherein the average fiber diameter of the modified cellulose fiber is 1 nm to 200 nm.

[0187] <6> According to the above <1> ~ <5> The composition according to any one of claims , wherein the average fiber diameter of the modified cellulose fibers is 1 nm to 150 nm.

[0188] <7> According to the above <1> ~ <6> The composition according to any one of claims , wherein the average fiber diameter of the modified cellulose fibers is 1 nm to 120 nm.

[0189] <8> According to the above <1> ~ <7> The composition according to any one of claims , wherein the average fiber diameter of the modified cellulose fibers is 1 nm to 20 nm.

[0190] <9> According to the above <1> ~ <8> The composition according to any one of claims , wherein the average aspect ratio of the modified cellulose fibers is 5 or more and 200 or less.

[0191] <10> According to the above <1> ~ <9> The composition according to any one of claims , wherein the average aspect ratio of the modified cellulose fibers is 5 or more and 150 or less.

[0192] <11> According to the above <1> ~ <10> The composition according to any one of claims , wherein the average aspect ratio of the modified cellulose fiber is 5 or more and 100 or less.

[0193] <12> According to the above <1> ~ <11> The composition according to any one of claims , wherein the average aspect ratio of the modified cellulose fibers is 5 or more and 70 or less.

[0194] <13> According to the above <1> ~ <12> The composition according to any one of the above, wherein the modified cellulose fiber has a crystallinity of 10% to 90%.

[0195] <14> According to the above <1> ~ <13> The composition according to any one of the above, wherein the modified cellulose fiber has a crystallinity of 10% to 85%.

[0196] <15> According to the above <1> ~ <14> The composition according to any one of the above, wherein the modified cellulose fiber has a crystallinity of 10% to 80%.

[0197] <16> according to <1> ~ <15> The composition according to any one of the above, wherein the modified cellulose fiber is a modified cellulose fiber in which a modifying group is bonded to the cellulose fiber,

[0198] The modifying group includes one or more selected from the group consisting of (a) a hydrocarbon group, (b) a silicone chain, and (c) an alkylene oxide chain.

[0199] <17> according to <16> The composition described in , wherein the cellulose fiber is anionically modified cellulose fiber.

[0200] <18> according to <16> or <17> The composition described in , wherein the modifying group is bonded to the anionic group of the anionically modified cellulose fiber via an ionic bond and / or a covalent bond.

[0201] <19> According to the above <16> ~ <18> The composition according to any one of the above, wherein the resin is a curable resin, preferably a thermosetting resin.

[0202] <20> According to the above <16> ~ <19> The composition according to any one of the above, wherein the resin is one or more resins selected from epoxy resins, urethane resins, acrylic resins, phenoxy resins, phenolic resins, urea resins and melamine resins.

[0203] <21> According to the above <16> ~ <20> The composition according to any one of the above, wherein the mass ratio of modified cellulose fiber / resin, calculated as cellulose (excluding modifying groups etc.) (when cellulose has an anionic group, calculated as anionic modified cellulose), is 0.01 / 100 or more and 30 / 100 or less.

[0204] <22> According to the above <16> ~ <21> The composition according to any one of the above, wherein the mass ratio of modified cellulose fiber / resin, calculated as cellulose (excluding modifying groups etc.) (wherein, when cellulose has an anionic group, it is converted to anionic modified cellulose), is 0.05 / 100 or more and 15 / 100 or less.

[0205] <23> According to the above <16> ~ <22> The composition according to any one of the above, wherein the mass ratio of the modified cellulose fiber / resin is calculated as cellulose (excluding modifying groups, etc.) (wherein, when the cellulose has anionic groups, it is converted to anionic modified cellulose), and is more preferably 0.1 / 100 or more and 10 / 100 or less.

[0206] <24> According to the above <16> ~ <23> The composition described in any one of the above is a structural adhesive.

[0207] <25> According to the above <16> ~ <24> The composition according to any one of the above, wherein the bonding surface of the structure comprises one or more selected from metal, plastic, ceramic and glass.

[0208] <26> According to the above <16> ~ <25> The composition according to any one of the above, which is used for bonding vehicle assembly products.

[0209] <27> According to the above <16> ~ <26> The composition according to any one of the above, which is used in a spot welding bonding process.

[0210] <28> According to the above <16> ~ <27> The composition described in any one of the above is an adhesive for metal components (for bonding metal components).

[0211] <29> According to the above <16> ~ <28> The composition according to any one of claims 1 to 5, wherein the bonding surface of the metal member includes a metal having a linear expansion coefficient of 20×10 -6 / ℃ and above metals.

[0212] <30> According to the above <16> ~ <29> The composition described in any one of claims , wherein the bonding surface of the metal member contains aluminum.

[0213] <31> According to the above <16> ~ <30> The composition described in any one of the above is used for bonding dissimilar metals.

[0214] <32> According to the above <16> ~ <31> The composition described in any one of the above is used for bonding dissimilar metals having different linear expansion coefficients.

[0215] <33> According to the above <16> ~ <32> The composition according to any one of the above, which is used for -6 / ℃ and the linear expansion coefficient is less than 20×10 -6 / ℃ metal bonding.

[0216] <34> According to the above <16> ~ <33> The composition described in any one of the above, which is used in combination of a metal containing iron and a metal containing aluminum.

[0217] <35> A bonding method, which uses an adhesive composition containing modified cellulose fibers and a resin to bond a structure.

[0218] The modified cellulose fibers have a cellulose I-type crystal structure, an average fiber length of 1000 nm or less, and an average fiber diameter of 1 nm to 300 nm or less.

[0219] <36> According to the above <35> The bonding method described in , wherein the bonding surface of the structure comprises one or more selected from metal, plastic, ceramic and glass.

[0220] <37> A bonding method for bonding metal components using an adhesive composition containing modified cellulose fibers and a resin.

[0221] The modified cellulose fibers have a cellulose I-type crystal structure, an average fiber length of 1000 nm or less, and an average fiber diameter of 1 nm to 300 nm or less.

[0222] <38> According to the above <35> ~ <37> The bonding method according to any one of the preceding claims, wherein the bonding surface of the metal member includes a metal member having a linear expansion coefficient of 20×10 -6 / ℃ and above metals.

[0223] <39> According to the above <35> ~ <38> The bonding method described in any one of claims , wherein the bonding surface of the metal member contains aluminum.

[0224] <40> According to the above <35> ~ <39> The bonding method described in any one of the above is used for bonding dissimilar metals.

[0225] <41> According to the above <35> ~ <40> The bonding method described in any one of the above is used for bonding dissimilar metals having different linear expansion coefficients.

[0226] <42> According to the above <35> ~ <41> The bonding method according to any one of the preceding claims, which is used for bonding a substrate having a linear expansion coefficient of 20×10 -6 / ℃ and the linear expansion coefficient is less than 20×10 -6 / ℃ metal bonding.

[0227] <43> According to the above <35> ~ <42> The bonding method according to any one of the above, which is used for a combination of a metal containing iron and a metal containing aluminum.

[0228] <44> According to the above <35> ~ <43> The bonding method according to any one of the preceding claims, wherein the adhesive composition is applied to the structure by discharging the adhesive composition from a dispenser.

[0229] <45> According to the above <35> ~ <44> The bonding method according to any one of claims , wherein the resin is a curable resin, preferably a thermosetting resin.

[0230] <46> According to the above <35> ~ <45> The bonding method according to any one of the preceding claims, wherein the resin is one or more resins selected from the group consisting of epoxy resins, urethane resins, acrylic resins, phenoxy resins, phenolic resins, urea resins, and melamine resins.

[0231] <47> According to the above <35> ~ <46> The bonding method according to any one of the above, wherein the mass ratio of modified cellulose fiber / resin, calculated as cellulose (excluding modifying groups, etc.) (wherein, when cellulose has anionic groups, it is converted to anionic modified cellulose), is 0.01 / 100 or more and 30 / 100 or less.

[0232] <48> According to the above <35> ~ <47> The bonding method according to any one of the above, wherein the mass ratio of the modified cellulose fiber / resin, calculated as cellulose (excluding modifying groups, etc.) (wherein, when the cellulose has anionic groups, it is converted to anionic modified cellulose), is 0.05 / 100 or more and 15 / 100 or less.

[0233] <49> According to the above <35> ~ <48> The bonding method described in any one of the above, wherein the mass ratio of modified cellulose fiber / resin is calculated as cellulose (excluding modifying groups, etc.) (wherein, when cellulose has anionic groups, it is converted to anionic modified cellulose), and is more preferably 0.1 / 100 or more and 10 / 100 or less.

[0234] <50> According to the above <35> ~ <49> The bonding method according to any one of the above, wherein the modified cellulose fiber is a modified cellulose fiber in which a modifying group is bonded to the cellulose fiber,

[0235] The modifying group includes one or more selected from the group consisting of (a) a hydrocarbon group, (b) a silicone chain, and (c) an alkylene oxide chain.

[0236] <51> According to the above <50> The bonding method described in , wherein the cellulose fiber is anionically modified cellulose fiber.

[0237] <52> According to the above <35> ~ <51> The bonding method according to any one of claims , wherein the average fiber length of the modified cellulose fibers is from 10 nm to 500 nm.

[0238] <53> According to the above <35> ~ <52> The bonding method according to any one of claims , wherein the average fiber length of the modified cellulose fibers is from 10 nm to 300 nm.

[0239] <54> According to the above <35> ~ <53> The bonding method according to any one of claims , wherein the average fiber length of the modified cellulose fibers is 10 nm or more and less than 150 nm.

[0240] <55> According to the above <35> ~ <54> The bonding method according to any one of claims , wherein the average fiber diameter of the modified cellulose fibers is 1 nm to 200 nm.

[0241] <56> According to the above <35> ~ <55> The bonding method according to any one of claims , wherein the average fiber diameter of the modified cellulose fibers is 1 nm to 150 nm.

[0242] <57> According to the above <35> ~ <56> The bonding method according to any one of claims , wherein the average fiber diameter of the modified cellulose fibers is 1 nm to 120 nm.

[0243] <58> According to the above <35> ~ <57> The bonding method according to any one of the above, wherein the average fiber diameter of the modified cellulose fibers is 1 nm to 20 nm.

[0244] <59> According to the above <35> ~ <58> The bonding method according to any one of claims , wherein the average aspect ratio of the modified cellulose fibers is 5 or more and 200 or less.

[0245] <60> According to the above <35> ~ <59> The bonding method according to any one of claims , wherein the average aspect ratio of the modified cellulose fibers is 5 or more and 150 or less.

[0246] <61> According to the above <35> ~ <60> The bonding method according to any one of claims , wherein the average aspect ratio of the modified cellulose fibers is 5 or more and 100 or less.

[0247] <62> According to the above <35> ~ <61> The bonding method according to any one of the above, wherein the average aspect ratio of the modified cellulose fibers is 5 or more and 70 or less.

[0248] <63> According to the above <35> ~ <62> The bonding method according to any one of claims 1 to 5, wherein the modified cellulose fiber has a crystallinity of 10% to 90%.

[0249] <64> According to the above <35> ~ <63> The bonding method according to any one of claims , wherein the modified cellulose fiber has a crystallinity of 15% to 85%.

[0250] <65> According to the above <35> ~ <64> The bonding method according to any one of claims , wherein the modified cellulose fiber has a crystallinity of 20% to 80%.

[0251] Example

[0252] The present invention will be described in detail below with reference to Examples etc. It should be noted that the following Examples are merely illustrative of the present invention and do not limit the present invention in any way. It should be noted that "normal pressure" means 101.3 kPa, and "normal temperature" means 25°C.

[0253] [Average fiber diameter, average fiber length and average aspect ratio of anionic modified cellulose fibers and modified cellulose fibers]

[0254] Water is added to the cellulose fibers to be measured to prepare a dispersion having a content of 0.0001% by mass. The dispersion is dripped onto mica and dried. The resulting material is used as an observation sample. An atomic force microscope (AFM) (Nanoscope II Tappingmode AFM manufactured by Digital Instruments; the probe uses Point Probe (NCH) manufactured by Nanosensors) to measure the fiber height (the difference in height between where the fibers are present and where the fibers are not present) of the cellulose fibers in the observation sample. At this time, 100 cellulose fibers are selected from the microscope image in which the cellulose fibers can be confirmed, and the average fiber diameter is calculated based on their fiber height. The average fiber length is calculated based on the distance in the fiber direction. It should be noted that the average fiber diameter and the average fiber length are number averages. The average aspect ratio is calculated based on the average fiber length / average fiber diameter. The height obtained by image analysis based on AFM can be regarded as the fiber diameter.

[0255] In Comparative Examples 3 and 4, it was difficult to confirm the modified cellulose fibers in the above-mentioned measurement using AFM. Therefore, in Comparative Examples 3 and 4, the obtained thickening composition was diluted with IPA to 0.02 wt%, and ultrasonic treatment was performed for 5 minutes, and 1 drop of the obtained solution was dripped on mica. After natural drying, gold sputtering was performed using MSP-1S (manufactured by Vacuum Equipment Co., Ltd.), and the obtained sample was observed using an electron microscope VE-8800 (manufactured by KEYENCE) under the measurement conditions of an acceleration voltage of 5 kV and a spot diameter of 8.

[0256] [Average fiber diameter and average fiber length of raw cellulose fibers]

[0257] Deionized water was added to the cellulose fibers to be measured to prepare a dispersion having a content of 0.01% by mass. The dispersion was measured using a wet dispersion type image analysis particle size distribution meter (manufactured by Jasco International, trade name: IF-3200) under the conditions of front lens: 2x, telecentric zoom lens: 1x, image resolution: 0.835 μm / pixel, syringe inner diameter: 6515 μm, spacer thickness: 500 μm, image recognition mode: ghost, threshold: 8, analysis sample amount: 1 mL, sampling: 15%. More than 100 cellulose fibers were measured, and their average ISO fiber diameter was calculated as the average fiber diameter, and the average ISO fiber length was calculated as the average fiber length.

[0258] [Anionic modified cellulose fibers and anionic group content of modified cellulose fibers]

[0259] Take 0.5 g of dry mass of cellulose fiber as the object of measurement in a beaker, add deionized water or a mixed solvent of methanol / water = 2 / 1 (volume ratio) to make the total volume 55 mL, add 5 mL of 0.01M sodium chloride aqueous solution thereto to prepare a dispersion. Stir the dispersion until the cellulose fiber as the object of measurement is fully dispersed. Add 0.1M hydrochloric acid to the dispersion to adjust the pH to 2.5-3, use an automatic titrator (manufactured by DKK East Asia, trade name "AUT-701"), add 0.05M sodium hydroxide aqueous solution to the dispersion with a waiting time of 60 seconds, and measure the conductivity and pH values ​​every 1 minute. Continue the measurement until the pH reaches about 11 to obtain a conductivity curve. The sodium hydroxide titration amount is calculated based on the conductivity curve, and the anionic group content of the cellulose fiber as the object of measurement is calculated using the following formula.

[0260] Anionic group content (mmol / g) = [amount of sodium hydroxide aqueous solution titration (mL) × concentration of sodium hydroxide aqueous solution (0.05 M)] / [mass of cellulose fiber to be measured (0.5 g)]

[0261] [Aldehyde content of oxidized cellulose fiber]

[0262] The carboxyl group content of the oxidized cellulose fibers to be measured was measured by the above-mentioned method for measuring the anionic group content.

[0263] On the other hand, 100 g of an aqueous dispersion of oxidized cellulose fibers to be measured (solid content 1.0% by mass), 100 g of an acetic acid buffer solution (pH 4.8), 0.33 g of 2-methyl-2-butene, and 0.45 g of sodium chlorite were added to a beaker and stirred at 25° C. for 16 hours to perform oxidation treatment of the aldehyde groups remaining in the oxidized cellulose fibers. After the reaction was completed, the cellulose fibers were washed with deionized water to obtain cellulose fibers in which the aldehyde groups were oxidized. The carboxyl content of the dried product obtained by freeze-drying was measured by the above-mentioned method for measuring the content of anionic groups, and the "carboxyl content of the oxidized cellulose fibers after oxidation treatment" was calculated. Next, the aldehyde content of the oxidized cellulose fibers to be measured was calculated by Formula 1.

[0264] Aldehyde content (mmol / g) = (carboxyl content of oxidized cellulose fibers after oxidation treatment) - (carboxyl content of oxidized cellulose fibers to be measured) Formula 1

[0265] 〔Solid content in dispersion〕

[0266] The measurement was performed using a halogen moisture meter (manufactured by Shimadzu Corporation; trade name "MOC-120H"), with 1 g of the sample being kept at 150°C and measured every 30 seconds, and the value at which the mass reduction became 0.1% or less of the initial amount of the sample was defined as the solid content.

[0267] [Bonding amount and introduction rate of modifying groups in modified cellulose fibers]

[0268] The following IR measurement method is used to determine the bonding amount of the modifying group, and the bonding amount and introduction rate are calculated using the following formula. Regarding IR measurement, specifically, an infrared absorption spectrometer (IR) (manufactured by Thermo Fisher Scientific, Nicolet 6700) is used to measure the infrared absorption spectrum of the dried modified cellulose fiber using the ATR method, and the bonding amount and introduction rate of the modifying group are calculated using formulas A and B. The following shows the case where the anionic group is a carboxyl group, that is, the case of oxidized cellulose fiber. The following "1720cm -1 The peak intensity "is the peak intensity derived from the carbonyl group. It should be noted that, in the case of anionic groups other than the carboxyl group, the bonding amount and introduction rate of the modifying group may be calculated by appropriately changing the value of the wave number.

[0269] <Formula A-1 (in the case of ionic bond)>

[0270] The bonding amount of the modifying group (mmol / g) = a × (bc) ÷ b

[0271] a: Carboxyl content of oxidized cellulose fiber (mmol / g)

[0272] b: 1720cm of oxidized cellulose fiber -1 The peak intensity

[0273] c: 1720cm of modified cellulose fiber -1 The peak intensity

[0274] <Formula A-2 (in the case of amide bond)>

[0275] The bonding amount of the modification group (mmol / g) = de

[0276] d: Carboxyl content of oxidized cellulose fiber (mmol / g)

[0277] e: carboxyl content of modified cellulose fiber (mmol / g)

[0278] <Formula B>

[0279] Introduction rate of modifying groups (mol%) = 100 × f / g

[0280] f: bonding amount of the modification group (mmol / g)

[0281] g: carboxyl content of oxidized cellulose fiber (mmol / g)

[0282] [Confirmation of the crystal structure of modified cellulose fibers]

[0283] The crystal structure of the modified cellulose fiber was confirmed by measuring using an X-ray diffractometer (MiniFlexII manufactured by Rigaku Corporation) under the following conditions.

[0284] The measurement conditions were as follows: X-ray source: Cu / Kα-radiation, tube voltage: 30 kV, tube current: 15 mA, measurement range: diffraction angle 2θ = 5 to 45°, X-ray scanning speed: 10° / min. As a sample for measurement, the cellulose fiber to be measured was compressed to an area of ​​320 mm 2 In addition, the crystallinity of the cellulose I-type crystal structure was calculated based on the following formula C using the obtained X-ray diffraction intensity.

[0285] <Formula C>

[0286] Cellulose I crystallinity (%) = [(I 22.6 -I 18.5 ) / I 22.6 ]×100

[0287] 〔In the formula, I 22.6 represents the diffraction intensity of the lattice plane (002 plane) (diffraction angle 2θ = 22.6°) in X-ray diffraction, I 18.5 represents the diffraction intensity of the amorphous part (diffraction angle 2θ = 18.5°)]

[0288] On the other hand, when the crystallinity obtained by the above formula C is 35% or less, from the viewpoint of improving the calculation accuracy, it is preferably calculated based on the following formula D in accordance with the description on pages 199-200 of the "Handbook of Wood Science Experiments" (edited by the Japan Wood Society; published in April 2000).

[0289] Therefore, when the crystallinity obtained by the above formula C is 35% or less, the value calculated based on the following formula D can be used as the crystallinity.

[0290] <Formula D>

[0291] Cellulose I crystallinity (%) = [A c / (A c +A a )]×100

[0292] 〔In the formula, A cA represents the sum of the peak areas of the lattice planes (002 plane) (diffraction angle 2θ = 22.6°), (011 plane) (diffraction angle 2θ = 15.1°), and (0-11 plane) (diffraction angle 2θ = 16.2°) in X-ray diffraction. a The peak area of ​​the amorphous part (diffraction angle 2θ = 18.5°) is obtained by fitting the obtained X-ray diffraction pattern with a Gaussian function.

[0293] [Cellulose fiber in modified cellulose fiber (converted amount)]

[0294] The amount of cellulose in the modified cellulose fiber (converted amount) refers to the amount of cellulose excluding the modifying group in the modified cellulose fiber. Since the modified cellulose fiber of the present invention sometimes has a formula weight of a modifying group that is considerably larger (for example, larger than the molecular weight of glucose), in this specification, when it is more appropriate to explain without the difference in the formula weight of the modifying group, it is not expressed in terms of the amount of the modified cellulose fiber, but in terms of the amount of cellulose constituting the modified cellulose fiber (converted amount).

[0295] The cellulose fibers (converted amount) in the modified cellulose fibers were measured by the following method.

[0296] (1) When only one "modifying compound" is added

[0297] The cellulose fiber amount (converted amount) was calculated using the following formula E.

[0298] <Formula E>

[0299] Cellulose fiber amount (converted amount) (g) = mass of modified cellulose fiber (g) / [1 + molecular weight of the modifying compound (g / mol) × bonding amount of the modifying group (mmol / g) × 0.001]

[0300] (2) When there are two or more "modifying compounds" added

[0301] The amount of cellulose fibers (converted amount) was calculated in consideration of the molar ratio of each compound (that is, the molar ratio when the total molar amount of the added compounds is taken as 1).

[0302] Production Example 1 (Production of anion-modified fine cellulose fibers)

[0303] After 10 g of bleached kraft pulp of a coniferous tree (manufactured by West Fraser, trade name: Hinton) as a natural cellulose was fully stirred in 990 g of ion exchange water, 0.13 g of 2,2,6,6-tetramethylpiperidine 1-oxide (TEMPO, manufactured by ALDRICH, 98 mass %), 1.3 g of sodium bromide, and 27 g of a 10.5 mass % aqueous sodium hypochlorite solution (10.5 mass % aqueous solution) were added in this order to 10 g of the pulp.

[0304] At this time, a 0.5M sodium hydroxide aqueous solution was added dropwise using an automatic titrator (manufactured by DKK Co., Ltd., AUT-701) using pH potentiometric titration to maintain the pH at 10.5. After reacting for 120 minutes (20°C) at a stirring speed of 200 rpm, the mixture was fully washed with ion exchange water and then dehydrated to obtain an anionic modified cellulose fiber having a solid content of 27.2%. The anionic group of the obtained anionic modified cellulose fiber was a carboxyl group, and the carboxyl group content was 1.3 mmol / g.

[0305] Production Example 2 (Production of Adhesive Composition Containing Modified Cellulose Fiber)

[0306] The anion-modified cellulose fibers obtained in Manufacturing Example 1, which are 2.0 g in terms of absolute dry mass, and 193 g of ion-exchanged water are mixed and stirred at room temperature (25°C) for 30 minutes using a mechanical stirrer. Next, 4.5 g of a 1M hydrochloric acid aqueous solution is added thereto and stirred at room temperature for 1 hour to react. After the reaction is completed, the mixture is thoroughly washed with ion-exchanged water until the filtrate is less than 200 μs / cm in the conductivity measurement using a compact conductivity meter (LAQUAtwin EC-33B manufactured by Horiba, Ltd.), thereby removing the hydrochloric acid and the generated salts. Thereafter, the solvent is replaced with 1-methoxy-2-propanol (PGME) to obtain an anion-modified fine cellulose fiber dispersion (solid content concentration 2.0%) in which the fine cellulose fibers containing carboxyl groups are swollen in PGME.

[0307] With respect to 21.4 g of the obtained dispersion, 0.27 g of monoamine (Jeffamine M-2070 manufactured by Huntsman, USA, PO / EO (molar ratio) = 10 / 31) was mixed, and stirred at 25°C for 1 hour to obtain a dispersion of modified cellulose fibers. Thereafter, 20 g of epoxy resin A (manufactured by Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, jER828, viscosity 120-150P / 25°C, epoxy equivalent 184-194) was added, and stirred at 25°C for another hour. The obtained mixed solution was subjected to five dispersion treatments at 150 MPa using a high-pressure homogenizer (manufactured by Yoshida Machinery Co., Ltd., Nano Vator L-ES).

[0308] The solvent is removed from the obtained dispersion to obtain a resin composition containing modified cellulose fibers and an epoxy resin.

[0309] The modified cellulose fiber obtained had a bonding amount of the modifying group (a group at the position where the alkyl group is bonded to the (EO / PO) chain) of 0.30 mmol / g, an introduction rate of the modifying group of 23.4 mol%, a cellulose type I crystallinity of 60%, an average fiber diameter of 2.7 nm, an average fiber length of 594 nm, and an average aspect ratio of 220. The physical properties of the modified cellulose obtained by the same dispersion process except for the addition of the resin were measured, thereby obtaining the above-mentioned physical properties of the modified cellulose. The same applies to the following. Here, the above-mentioned monoamine is a monoamine having an alkylene oxide chain, i.e., a (EO / PO) chain.

[0310] Production Example 3 (Production of a Resin Composition Containing Short-Fiber Modified Cellulose Fibers)

[0311] The anion-modified cellulose fiber obtained in the manufacturing example 1 with an absolute dry mass of 2.0g and ion exchange water 193g were mixed and stirred at room temperature (25°C) for 30 minutes using a mechanical stirrer. Next, 24.5g of 1M hydrochloric acid aqueous solution was added thereto and stirred at room temperature for 1 hour to react. After the reaction was completed, the ion exchange water was fully washed until the filtrate was less than 200μs / cm in the conductivity measurement using a compact conductivity meter (LAQUAtwin EC-33B manufactured by Horiba, Ltd.), thereby removing hydrochloric acid and the generated salt. Thereafter, the obtained anion-modified cellulose fiber with an absolute dry mass of 1.8g was added to a sample bottle equipped with a magnetic stirrer and a stirrer, and ion exchange water was added until the mass of the treated solution was 36g. The treated solution was reacted at 95°C for 12 hours to obtain an aqueous suspension of short-fibered anion-modified cellulose fibers.

[0312] Thereafter, the solvent was replaced with PGME to obtain a short-fibered anionic modified cellulose fiber dispersion (solid content concentration 2.0%) in which the carboxyl-containing cellulose fibers were swollen in PGME. 0.27 g of monoamine (Jeffamine M-2070, PO / EO (molar ratio) = 10 / 31, manufactured by Huntsman, USA) was mixed with 21.4 g of the obtained dispersion and stirred at 25°C for 1 hour to obtain a dispersion of short-fibered modified cellulose fibers. Thereafter, 20 g of epoxy resin A was added and stirred at 25°C for another hour. The obtained mixed solution was subjected to 5 dispersion treatments at 150 MPa using a high-pressure homogenizer (Nano Vator L-ES manufactured by Yoshida Machinery Co., Ltd.).

[0313] The solvent was removed from the obtained dispersion to obtain a resin composition containing short-fibered modified cellulose fibers and an epoxy resin. The modified cellulose fibers obtained had a bonding amount of 0.30 mmol / g of the modified group (a group at the alkyl group bonded to the (EO / PO) chain position), an introduction rate of 23.4 mol%, a cellulose I-type crystallinity of 65%, an average fiber length of 132 nm, an average fiber diameter of 3.3 nm, and an average aspect ratio of 40.

[0314] Production Example 4 (Production of long-fiber anionically modified fine cellulose fibers)

[0315] After 8 g of bleached kraft pulp of a coniferous tree (manufactured by West Fraser, trade name: Hinton) as a natural cellulose was fully stirred with 760 g of ion exchange water, 0.09 g of TEMPO (manufactured by ALDRICH, free radical, 98% by mass), 1.0 g of sodium bromide, and 21 g of a 5.0% by mass sodium hypochlorite aqueous solution (3.8 mmol / g relative to 1 g of pulp) were added in this order to 8 g of the pulp.

[0316] At this time, a 0.5 M sodium hydroxide aqueous solution was added dropwise using a pH potentiometric titration apparatus (manufactured by DKK Toa Co., Ltd., AUT-701) to maintain the pH at 10.5. After the reaction was carried out at a stirring speed of 200 rpm for 120 minutes (20° C.), the addition of sodium hydroxide was stopped to obtain a suspension of anionic modified cellulose fibers (i.e., oxidized cellulose fibers) whose anionic groups are carboxyl groups.

[0317] After adding 0.01M hydrochloric acid to the obtained suspension of anionic modified cellulose fibers to adjust the pH to 2, the anionic modified cellulose fibers were fully washed with ion exchange water until the conductivity of the filtrate measured by a compact conductivity meter (LAQUAtwin EC-33B manufactured by Horiba, Ltd.) was 200μs / cm or less, and then dehydrated to obtain cake-like anionic modified cellulose fibers. The carboxyl content of the obtained anionic modified cellulose fibers was 1.3mmol / g.

[0318] Ion exchange water was added to the obtained anionic modified cellulose fibers so that the solid content concentration was 0.5%, and the mixture was stirred at 25°C for 1 hour. With respect to 80 g of the obtained dispersion, 0.27 g of monoamine (Jeffamine M-2070, PO / EO (molar ratio) = 10 / 31, manufactured by Huntsman, USA) was mixed, and the mixture was stirred at 25°C for 1 hour to obtain a dispersion of modified cellulose fibers. The obtained mixed solution was subjected to a dispersion treatment at 100 MPa once using a high-pressure homogenizer (Nano Vator L-ES manufactured by Yoshida Machinery Co., Ltd.). Thereafter, PGME was added so that the solid content concentration was 0.17%, and the mixture was stirred at 25°C for another hour. The obtained mixed solution was subjected to a dispersion treatment at 100 MPa once using a high-pressure homogenizer.

[0319] While adding PGME to the obtained dispersion, the ion exchange water is removed to obtain a PGME dispersion of modified cellulose fibers, and then 20 g of epoxy resin A is added to the obtained dispersion and stirred at 25°C for 1 hour. The obtained mixed solution is subjected to a dispersion treatment at 50 MPa using a high-pressure homogenizer. The solvent is removed from the obtained dispersion to obtain a resin composition containing an epoxy resin. The bonding amount of the modified group (the group at the alkyl bonded (EO / PO) chain position) of the obtained modified cellulose fiber is 0.30 mmol / g, the introduction rate of the modified group is 23.4 mol%, the cellulose I type crystallinity is 43%, the average fiber length is 4870 nm, the average fiber diameter is 111 nm, and the average aspect ratio is 44.

[0320] Examples 1 and 2 (Manufacturing of Adhesive Composition)

[0321] To 10 g of the resin composition obtained in Preparation Example 3, 0.5 g of dicyandiamide (addition polymerization curing agent) and 0.3 g of 3-(3,4-dichlorophenyl)-1,1-dimethylurea (curing accelerator, manufactured by Hodogaya Chemical Industry Co., Ltd.: DCMU99) were added, and the mixture was stirred at room temperature (25°C) for 2 minutes using a rotary-revolution mixer (manufactured by Thinky Co., Ltd., Degassing Rentaro) and degassed for 2 minutes to obtain an adhesive composition containing modified cellulose fibers and an epoxy resin.

[0322] Embodiment 3, 4

[0323] In Examples 1 and 2, except that the resin composition 10 g obtained in Production Example 2 was used instead of the resin composition 10 g obtained in Production Example 3, an adhesive composition was obtained in the same manner as in Examples 1 and 2.

[0324] Embodiment 5, 6

[0325] Adhesive compositions were obtained in the same manner as in Examples 1 and 2 except that modified cellulose fibers having an amino-modified silicone (SS-3551 manufactured by Dow Corning-Toray Silicone Co., Ltd.) as a modifying group were used instead of 10 g of the resin composition obtained in Production Example 3.

[0326] Embodiment 7, 8

[0327] Adhesive compositions were obtained in the same manner as in Examples 3 and 4 except that, as the type of resin contained in the resin composition 10 g obtained in Production Example 2, a resin composition 10 g obtained by mixing epoxy resin A and acrylic resin (NeoCryl A-1127) at a ratio of 95 mass % and 5 mass %, respectively, was used.

[0328] Comparative Examples 1 and 2

[0329] In Examples 1 and 2, adhesive compositions were obtained in the same manner as in Examples 1 and 2 except that 10 g of the epoxy resin A containing no modified cellulose fiber was used instead of 10 g of the resin composition obtained in Production Example 3.

[0330] Comparative Examples 3 and 4

[0331] In Examples 1 and 2, except that the resin composition 10 g obtained in Production Example 4 was used instead of the resin composition 10 g obtained in Production Example 3, an adhesive composition was obtained in the same manner as in Examples 1 and 2.

[0332] [Evaluation of physical properties]

[0333] The properties of the obtained adhesive composition were evaluated by the methods of the following Test Examples 1 and 2. The results are shown in Tables 1 to 3.

[0334] Test Example 1 (shear bond strength test: same type of bonding)

[0335] According to the shear strength test method described in JASO M353, the obtained adhesive composition was applied to the adherend with a coating thickness of 0.15 mm, that is, the overlap of two cold-rolled steel plates SPCC-SD (100 mm × 25 mm × 1.6 mm) as the bonding surface was 12.5 mm, and after removing the exuded adhesive composition, it was heated and cured at 130°C for 2 hours to prepare a shear test piece. The obtained test piece was tested using a desktop precision universal testing machine (AGS-X manufactured by Shimadzu Corporation) under the conditions of a chuck distance of 111.5 cm, room temperature (25°C), and a tensile speed of 5 mm / min.

[0336] It should be noted that, regarding the surface treatment method before use of the cold-rolled steel sheet SPCC-SD used herein, the steel sheet was degreased with acetone, dried, immersed in rust-proof oil (WD-40), and then left for 24 hours to remove the oil, and the steel sheet obtained in this way was used.

[0337] The numerical value of the shear bond strength is expressed as an index when the value of the adhesive composition obtained in Examples 1, 3, 5, 7 and Comparative Example 3 is set to 100.

[0338] Test Example 2 (Shear Bond Strength Test: Dissimilar Bonding)

[0339] The test was conducted in the same manner as in Test Example 1 except that one cold-rolled steel sheet SPCC-SD and one aluminum alloy sheet A5052P were used instead of two cold-rolled steel sheets SPCC-SD in Test Example 1.

[0340] The numerical value of the shear bond strength is expressed as an index when the value of the adhesive composition obtained in Examples 2, 4, 6, and 8 is set to 100 for the adhesive composition obtained in Comparative Example 2.

[0341] Test Example 3 (Evaluation of Discharging Property)

[0342] The ejection property of the adhesive composition can be qualitatively evaluated by an ejection test using a testing machine. Here, 0.5 g of the sample is filled in a 2 mL syringe, and the mixture is squeezed out by hand at room temperature to evaluate whether the viscosity is within the ejection-capable range.

[0343] Evaluation Benchmarks

[0344] A: Can spit out

[0345] B: Difficult to spit out (can be spit out to a certain extent with one hand)

[0346] C: Difficult to spit out (can be spit out to a certain extent using both hands)

[0347] D: Unable to spit out

[0348] [Table 1]

[0349]

[0350] *1: Mass ratio of unmodified cellulose fiber to curable resin (A)

[0351] [Table 2]

[0352]

[0353] *1: Mass ratio of unmodified cellulose fiber to curable resin (A)

[0354] [Table 3]

[0355]

[0356] *1: Mass ratio of unmodified cellulose fiber to curable resin (A)

[0357] Tables 1 to 3 show that the adhesive compositions of the present invention containing modified cellulose fibers having an average fiber length of 1000 nm or less as in Examples 1 to 8 have improved shear bond strength compared to the comparative examples and are suitable for structural adhesives.

[0358] Comparison between Examples 1 and 3, and Examples 2 and 4 shows that Examples 1 and 2 using modified cellulose fibers having a short average fiber length and a small average aspect ratio have excellent bonding strength and excellent ejectability.

[0359] Compared with the comparison between Example 1 and Comparative Example 1 (the bonding strength is 1.3 times), it can be seen from the comparison between Example 2 and Comparative Example 2 (the bonding strength is 7.2 times) that the adhesive composition of the present invention has excellent adhesion between materials with different physical properties (for example, different materials including metals with large linear expansion coefficients).

[0360] Industrial Applicability

[0361] The adhesive composition of the present invention can be used for structural bonding of vehicle assembly products and the like.

Claims

1. An adhesive composition comprising modified cellulose fiber and a resin, The modified cellulose fiber has a cellulose I-type crystal structure, an average fiber length of less than 150 nm, and an average fiber diameter of 1 nm to 20 nm. Modified cellulose fiber is made by bonding modified groups to cellulose fibers. The modifying group contains one or more selected from (a) a hydrocarbon group, (b) a silicone chain, and (c) an alkylene oxide chain. The average aspect ratio of the modified cellulose fibers is 20 or more and 100 or less, The average fiber length of the modified cellulose fibers is 50 nm or more. Cellulose type I refers to the crystal form of natural cellulose. The average aspect ratio is calculated from the average fiber length / average fiber diameter. The average fiber diameter and average fiber length are number averages and are calculated by the following measurement method: Method for measuring the average fiber diameter and the average fiber length: Water is added to the cellulose fibers to be measured to prepare a dispersion with a content of 0.0001 mass%, the dispersion is dropped onto mica and dried, the resulting material is used as an observation sample, and an atomic force microscope is used to measure the fiber height of the cellulose fibers in the observation sample, that is, the difference in height between where the fibers exist and where the fibers do not exist. At this time, 100 cellulose fibers are selected from the microscope image in which the cellulose fibers can be confirmed, and the average fiber diameter is calculated based on their fiber heights, and the average fiber length is calculated based on the distance in the fiber direction.

2. The adhesive composition according to claim 1, in, The mass ratio of modified cellulose fiber / resin in the composition is 0.01 / 100 or more and 30 / 100 or less when converted to cellulose fiber containing no modifying group, and when the cellulose fiber has an anionic group, when converted to anionic modified cellulose fiber.

3. The adhesive composition according to claim 1, in, The mass ratio of modified cellulose fiber / resin in the composition is 0.5 / 100 or more and 3 / 100 or less when converted to cellulose fiber containing no modifying group, and when the cellulose fiber has an anionic group, when converted to anionic modified cellulose fiber.

4. The adhesive composition according to claim 1, in, The amount of the modified cellulose fibers in the composition is 0.01% by mass or more and 30% by mass or less, calculated as cellulose fibers not containing a modifying group, based on the amount of the fibers added.

5. The adhesive composition according to claim 1, in, The amount of the modified cellulose fibers in the composition is 0.5% by mass or more and 3% by mass or less, calculated as cellulose fibers not containing a modifying group, based on the amount of the fibers added.

6. The adhesive composition according to claim 1, in, The bonding amount of the modifying groups in the modified cellulose fibers is 0.01 mmol / g or more and 3.0 mmol / g or less.

7. The adhesive composition according to claim 1, in, The crystallinity of the modified cellulose fiber is greater than 10% and less than 90%. The crystallinity of the modified cellulose fiber is the cellulose type I crystallinity calculated based on the diffraction intensity value based on the X-ray diffraction method. The cellulose type I crystallinity refers to the proportion of the crystalline region in the entire cellulose fiber. The presence or absence of the cellulose type I crystal structure is determined by the presence of a peak at 2θ=22.6° in the X-ray diffraction measurement.

8. The adhesive composition according to claim 1, in, The crystallinity of the modified cellulose fiber is greater than 20% and less than 80%. The crystallinity of the modified cellulose fiber is the cellulose type I crystallinity calculated based on the diffraction intensity value based on the X-ray diffraction method. The cellulose type I crystallinity refers to the proportion of the crystalline region in the entire cellulose fiber. The presence or absence of the cellulose type I crystal structure is determined by the presence of a peak at 2θ=22.6° in the X-ray diffraction measurement.

9. The adhesive composition according to any one of claims 1 to 8, in, The cellulose fiber is anionically modified cellulose fiber.

10. The adhesive composition according to any one of claims 1 to 8, in, The modifying group is bonded to the anionic group of the anionically modified cellulose fiber via an ionic bond and / or a covalent bond.

11. The adhesive composition according to any one of claims 1 to 8, in, The resin is a curable resin.

12. The adhesive composition according to any one of claims 1 to 8, in, The resin is one or more resins selected from the group consisting of epoxy resins, urethane resins, acrylic resins, phenoxy resins, phenolic resins, urea resins, and melamine resins.

13. A bonding method, comprising bonding a structure using an adhesive composition comprising modified cellulose fibers and a resin, The modified cellulose fiber has a cellulose I-type crystal structure, an average fiber length of less than 150 nm, and an average fiber diameter of 1 nm to 20 nm. Modified cellulose fiber is made by bonding modified groups to cellulose fibers. The modifying group contains one or more selected from (a) a hydrocarbon group, (b) a silicone chain, and (c) an alkylene oxide chain. The average aspect ratio of the modified cellulose fibers is 20 or more and 100 or less, The average fiber length of the modified cellulose fibers is 50 nm or more. Cellulose type I refers to the crystal form of natural cellulose. The average aspect ratio is calculated from the average fiber length / average fiber diameter. The average fiber diameter and average fiber length are number averages and are calculated by the following measurement method: Method for measuring the average fiber diameter and the average fiber length: Water is added to the cellulose fibers to be measured to prepare a dispersion with a content of 0.0001 mass%, the dispersion is dropped onto mica and dried, the resulting material is used as an observation sample, and an atomic force microscope is used to measure the fiber height of the cellulose fibers in the observation sample, that is, the difference in height between where the fibers exist and where the fibers do not exist. At this time, 100 cellulose fibers are selected from the microscope image in which the cellulose fibers can be confirmed, and the average fiber diameter is calculated based on their fiber heights, and the average fiber length is calculated based on the distance in the fiber direction.

14. The bonding method according to claim 13, in, The structure is a metal component.

15. The bonding method according to claim 14, in, The bonding surface of the metal component includes aluminum.

16. A bonding method for bonding dissimilar metals using an adhesive composition containing modified cellulose fibers and a resin, The modified cellulose fiber has a cellulose I-type crystal structure, an average fiber length of less than 150 nm, and an average fiber diameter of 1 nm to 20 nm. Modified cellulose fiber is made by bonding modified groups to cellulose fibers. The modifying group contains one or more selected from (a) a hydrocarbon group, (b) a silicone chain, and (c) an alkylene oxide chain. The average aspect ratio of the modified cellulose fibers is 20 or more and 100 or less, The average fiber length of the modified cellulose fibers is 50 nm or more. Cellulose type I refers to the crystal form of natural cellulose. The average aspect ratio is calculated from the average fiber length / average fiber diameter. The average fiber diameter and average fiber length are number averages and are calculated by the following measurement method: Method for measuring the average fiber diameter and the average fiber length: Water is added to the cellulose fibers to be measured to prepare a dispersion with a content of 0.0001 mass%, the dispersion is dropped onto mica and dried, the resulting material is used as an observation sample, and an atomic force microscope is used to measure the fiber height of the cellulose fibers in the observation sample, that is, the difference in height between where the fibers exist and where the fibers do not exist. At this time, 100 cellulose fibers are selected from the microscope image in which the cellulose fibers can be confirmed, and the average fiber diameter is calculated based on their fiber heights, and the average fiber length is calculated based on the distance in the fiber direction.

17. The bonding method according to claim 16, in, Dissimilar metals have different linear expansion coefficients.

18. The bonding method according to claim 17, wherein the bonding line expansion coefficient is 20×10 -6 / ℃ and the linear expansion coefficient is less than 20×10 -6 / ℃ metal.